Mixed Ligand Alkaline Earth Metal Complexes - Rao, T.V.R.K.; Das, B.N. (Asian Journal of Chemistry, 2010)
Mixed Ligand complexes of magnesium and calcium with some chelating organic acids. viz., salicylaldehyde, salicylic acid, anthranilic acid or 8-hydroxy quinoline as primary ligands and vanilline as secondary ligand, have been synthesised and characterised.